Preparation of PLGA microspheres loaded with 10-hydroxycamptothecin and arsenic trioxide and their treatment for rabbit hepatocellular carcinoma - Wu, Yumin; Du, Duanming; Chen, Juanping; Liu, Chunlin (Biomedical papers, 2021)
Objective. This study aims to study the preparation method of arsenic trioxide (As2O3) polylactic-co-glyconlic acid (PLGA) microspheres and 10-hydroxycamptothecin (HCPT) PLGA microspheres and explore their therapeutic effects as embolic agents for VX2 hepatocellular carcinoma in rabbits. Methods. As2O3 and HCPT PLGA microspheres were prepared by multiple emulsion solvent evaporation method. Scanning electron microscopy (SEM) and particle size distribution were used to analyze the morphology, the drug sustained release ability was observed by the release of microspheres in vitro. The rabbit model of VX2 hepatocellular carcinoma was established and the hepatocellular carcinoma was treated with combined microspheres. The therapeutic effects were detected by qPCR, western blotting, HE staining and immunohistochemical methods. Results. The PLGA microspheres loaded with As2O3 and HCPT were successfully prepared by optimizing the ratio. The particle size was between 30 and 50 μm. In vitro release results showed that PLGA microspheres loaded with As2O3 released completely in 10 days and PLGA microspheres loaded with HCPT released completely in 12 days. Western blotting and qPCR results showed that the expression of ALDH1A1 and Nanog decreased significantly in treatment group. HE staining and immunohistochemical analysis showed that the expression of CD31, HIF and VEGF decreased significantly and the apoptosis of tissues was obvious. Conclusion. The combination of As2O3 and HCPT PLGA microspheres as embolization for VX2 hepatocellular carcinoma in rabbits has significant therapeutic effect.
Keywords: polylactic-co-glyconlic acid (PLGA); arsenic trioxide (As2O3); 10-hydroxycamptothecin (HCPT); western blotting; Immunohistochemistry